Nitrogen alloyed steels – a new generation of materials with extraordinary properties. (4th August 2014) - Stein, G.; Menzel, J.
A new steel producing technique, based on pressurised electroslag remelting, has spawned a new generation of engineering materials, the nitrogen–alloyed steels. The paper describes the properties of these ferritic and austenitic N–alloyed steels and their potential for future applications, and compares the mechanical properties or the standard steel grades with the in which carbon is partially replaced by nitrogen. A number of clear advantages over carbon–containing steel are worth mentioning: (i) nitrogen in solid solution increases the strength and corrosion resistance or austenitic and ferritic–martensitic chrome–steels by way of solid–solution hardening: (ii) in the form of nitrides nitrogen induces precipitation hardening, which greatly improves the high–temperature strength and creep strength of heat–treatable steels; (iii) interstitially dissolved nitrogen improves strain hardening in austenitic steels when cold–worked and suppresses the formation of marrensite. Our research is therefore focused on the development of ultra–high–strength, stress–corrosion–cracking–resistant austenitic steels, high–hardness stainless heat treatable steels and high–temperature heat–treatable steels.